TAK ADE: Tutur Bahasa Basa-Basi pada Orang Melayu di Pulau Penyengat, Kota Tanjungpinang - Utami, Fathya Tyas Yudila; Meiyenti, Sri; Yunarti, Yunarti (Universitas Padjadjaran, 2024)
Small talk serves as a societal effort to foster interactions among individuals. This linguistic habit plays a vital role in maintaining the stability of social interactions. A similar phenomenon is observed in Pulau Penyengat, where small talk is deeply ingrained in the community's daily life. Instead of using the conventional phrase